2016
DOI: 10.1016/j.ijpara.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Entomopathogenic and plant pathogenic nematodes as opposing forces in agriculture

Abstract: Plant-parasitic nematodes (PPN) are responsible for substantial damages within the agriculture industry every year, which is a challenge that has thus far gone largely unimpeded. Chemical nematicides have been employed with varying degrees of success, but their implementation can be cumbersome, and furthermore they could potentially be neutralizing an otherwise positive effect from the entomopathogenic nematodes (EPN) that coexist with PPNs in soil environments and provide protection for plants against insect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…Some EPN isolates may be more effective against certain plant-parasitic nematode species, and some plant species may not be as attuned to the benefits of specific EPNs (Kenney and Eleftherianos, 2016). For this reason, it is important to consider new EPN isolates and compare the effect of different inoculation options of the nematode-bacterial symbiont complex.…”
Section: Introductionmentioning
confidence: 99%
“…Some EPN isolates may be more effective against certain plant-parasitic nematode species, and some plant species may not be as attuned to the benefits of specific EPNs (Kenney and Eleftherianos, 2016). For this reason, it is important to consider new EPN isolates and compare the effect of different inoculation options of the nematode-bacterial symbiont complex.…”
Section: Introductionmentioning
confidence: 99%
“…() found that EPNs could extend their ecological niche breadth by associating with different symbiotic bacteria. Therefore, the spectrum of ecological consequences that are mediated by EPB extends from influencing the surrounding soil biota to modifying the behaviour of the symbiotic nematodes (Kenney and Eleftherianos, ), which should cascade down to influence the whole soil community dynamics of interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Such multiple infections, although leading to competition between nematodes (see below), lower the risk of them being overcome by the host’s immune system. However, Kenney and Eleftherianos suggested that the success of infection of EPNs used in biocontrol programs could be improved by developing nematode-bacteria complexes that produce proteins necessary for evasion of the host’s immune system, or nematodes with a short delay in the ejection of their bacterial symbionts [ 157 ].…”
Section: Infectionmentioning
confidence: 99%
“…Because of their negative interaction on other nematodes, EPNs can be used to control pest species. Many studies already documented the efficacy of EPNs against pest nematodes (reviewed by Kenney and Eleftherianos [ 157 ]). For instance, several species of EPNs, and particularly their bacteria, proved to be efficient against the root-knot nematode Meloidogyne incognita , a parasite of tomato plants [ 179 , 180 , 181 ].…”
Section: Interaction With the Biotic And Abiotic Environmentmentioning
confidence: 99%